2022
DOI: 10.3389/fnimg.2022.971201
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant resting-state functional connectivity in incarcerated women with elevated psychopathic traits

Abstract: Previous work in incarcerated men suggests that individuals scoring high on psychopathy exhibit aberrant resting-state paralimbic functional network connectivity (FNC). However, it is unclear whether similar results extend to women scoring high on psychopathy. This study examined whether psychopathic traits [assessed via the Hare Psychopathy Checklist – Revised (PCL-R)] were associated with aberrant inter-network connectivity, intra-network connectivity (i.e., functional coherence within a network), and amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 77 publications
2
12
0
Order By: Relevance
“…The rsfMRI data was compressed using two stages of PCA ( Rachakonda et al, 2016 ). For the first data reduction step, we retained 100 principal components (PCs), and 50 independent components (ICs) for group data reduction, consistent with previously published studies ( Allen et al, 2011a , Allen et al, 2022 , Erhardt et al, 2011 , Elseoud et al, 2011 , Kiviniemi et al, 2009 , Smith et al, 2009 , Ystad et al, 2010 ). Individual specific spatial maps and their time-courses were obtained using gICA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rsfMRI data was compressed using two stages of PCA ( Rachakonda et al, 2016 ). For the first data reduction step, we retained 100 principal components (PCs), and 50 independent components (ICs) for group data reduction, consistent with previously published studies ( Allen et al, 2011a , Allen et al, 2022 , Erhardt et al, 2011 , Elseoud et al, 2011 , Kiviniemi et al, 2009 , Smith et al, 2009 , Ystad et al, 2010 ). Individual specific spatial maps and their time-courses were obtained using gICA.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the relationship of trauma to alternative resting-state activational measures, including amplitude of fluctuations (AFs), has been left unexplored in the literature. AFs may be particularly important to investigate, as they have been linked to psychiatric disorders, behavioral characteristics, and are thought to underlie functional connectivity more generally ( Allen et al, 2022 , Eggart et al, 2019 , Gazula et al, 2022 , Guo et al, 2013 , Weightman et al, 2019 , Wielaard et al, 2018 , Yue et al, 2015 , Zamani Esfahlani et al, 2020 ), By assessing aberrant global (inter-network) and local (intra-network and AFs) measures of trauma-related connectivity, a more thorough picture of the effects of trauma on the brain can be offered.…”
Section: Introductionmentioning
confidence: 99%
“…We found that interpersonal/affective psychopathic traits (e.g., deficient empathy, a lack of remorse, and manipulativeness) were associated with increased amplitude of low-frequency fluctuations (ALFFs) in executive control and attentional networks, decreased high-frequency ALFFs in executive control and visual networks, and decreased intra-network connectivity in the default mode network. Lifestyle/antisocial psychopathic traits were associated with decreased high-frequency ALFFs in executive control and default mode networks, and both increased and decreased intra-network functional connectivity in visual networks (Allen et al, 2022b ), diverging from similar analyses conducted in adult men scoring high on psychopathic traits which found no effects for the same measure (Espinoza et al, 2018 ). These results suggest potentially sex-specific neurobiological correlates of high-risk phenotypes, primarily occurring across regions and networks involved in socioemotional processing.…”
Section: Introductionmentioning
confidence: 94%
“…The relationship of psychopathic traits to other resting-state activational measures in incarcerated adolescent girls, including ALFFs, has been left unexplored. Due to their demonstrated association with functional connectivity more generally, and psychiatric disorders and behavioral characteristics, ALFFs may be a useful mode of investigation in relation to psychopathic traits (Guo et al, 2013 ; Yue et al, 2015 ; Wielaard et al, 2018 ; Eggart et al, 2019 ; Weightman et al, 2019 ; Zamani Esfahlani et al, 2020 ; Allen et al, 2022b ; Gazula et al, 2022 ). By assessing the relationship of psychopathic traits to measures previously examined in the literature—such as altered inter-network and intra-network functional connectivity—as well as those unexamined in the literature (ALFFs), a more thorough picture of how these traits relate to altered functional brain connectivity on a local and global scale in relation to adolescent girls can be offered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation